Efektifitas Strategi Reciprocal Teaching dan KWL terhadap Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - rifianti, silvia; Taufik, Taufina; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Writing this article aims to determine the effectiveness of Reciprocal Teaching strategy and KWL on the students' grade comprehension skills of grade VI SDN 30Cengkeh academic year 2017/2018.Metode used in this research is quasi experiment. The population in this study were all students of class VI SDN 30 Cengkeh, amounting to 69 students with a sample of class VIA and VIB, each consisting of 35 and 34 students. Sampling using a saturated sampling technique. The results showed that there is effectiveness of Reciprocal Teaching and KWL strategy on reading comprehension skills of grade VI students of SDN 30 Cengkeh Padang. This is evidenced from the t-test with a significant level of 5% obtained tcount (0.034)> ttable (1.667) so that H0 is accepted. Keywords: Reciprocal Teaching strategy, KWL Strategy, reading comprehension